The Soil Moisture Monitoring Utilize IoT System To Improve Urban Farming Productivity and Enhance Food Security - Mukhamad Kasendra; Dendy K Pramudito; Dedi Afandi (SEULANGA SYSTEM PUBLISHER, 2025)
Farming or planting is part of human efforts to meet food needs, but along the time agricultural land is decreasing where one of the causes is due to infrastructure development, such as road construction, office buildings and others, so that the threat of a food crisis has arisen. A new agricultural method or technique emerged by utilizing existing land such as home yards as a substitute for rice fields called urban farming or urban agriculture, where this agriculture technique is not only conducted in rural areas but also can be implemented in urban areas. Of course it is a good initiative, as one of the actions in dealing with the threat of a food crisis due to reduced agricultural land. However, during implementation, urban farmers find technical obstacles such as in monitoring or controlling soil conditions and with time limitation. With the improvement or innovation of technology and the availability of the internet, this should be able to solve the problem, considering that these two things have not yet utilized properly in terms of agricultural activities, such as the use of the internet by farmers which is generally used for communicating. One technology that can be used and solved that problem is the Internet of Things (IoT). IoT can be utilized in monitoring the humidity of the soil via smartphones in real time. So, the obstacles that arise can be resolved by utilizing IoT and of course for the future this technology can be developed according to the needs.